(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
This study explores the rich cultural heritage of Surkhandarya, Uzbekistan, focusing on its tradition of craftsmanship and the development of artisanal training courses. It examines the historical significance of Surkhandarya’s craftsmanship, including its influences from the Silk Road trade routes, as well as the contemporary challenges and opportunities facing the region’s artisanal sector. Through a multi-method approach involving literature review, field research, surveys, interviews, and collaborative workshops, the study provides insights into the preservation, promotion, and revitalization of Surkhandarya’s artisanal heritage. Key findings include the cultural significance of Surkhandarya’s crafts, the economic impact of artisanal training programs, and the importance of community engagement in sustaining traditional craftsmanship knowledge.